Explore, develop, innovate!: urban development for innovation economies - Zundel, Bryan Christopher (Kansas State University, 2013)
Some cities target innovation to bolster their economy, because it drives economic growth. An emerging trend is to use urban regeneration to accomplish this desire. However, lack of understanding about land development effects on innovation is a major concern. Such uncertainty makes it difficult to create visions, plans, and designs for these environments. A major dilemma presents itself. In what way do urban designers develop innovation economies and what confidence can they have in those roles considering the lack of evidence about urban sites within larger innovation systems? In response to the dilemma, this research documents projects facilitating innovation in local economies. A catalog was the tool for exploring characteristics of these places and their connections to economic systems. The catalog acts as a decision framework by displaying these relationships through a goal, objective, and tactic hierarchy. This format illustrates how site-level decisions impact specific parts of the economy. By using the catalog, planners and designers may guide innovation through urban development. To accomplish this, developments must draw talented people with creative ideas and organizations willing to invest in those ideas. When synergies form between these groups, new goods and services become available. To build this innovative milieu, planners and designers EXPLORE regional and site-based opportunities to determine the tactics they utilize. Next, they DEVELOP plans for the places desired by and required for people who INNOVATE. These findings collectively instill confidence in the roles of planners and designers in their quest to cultivate innovative environments.
Keywords: Innovation; Innovation district; Innovation economy; Urban design; Urban revitalization; Knowledge-Based Urban Development; Area Planning and Development (0341); Landscape Architecture (0390); Urban Planning (0999)